2022
DOI: 10.1097/gox.0000000000004603
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalmar Endoscopic versus Open Trigger Finger Release: Results from a Prospective Trial

Abstract: The trial is registered through www.clinicaltrials.gov (NCT03883477).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similar results have already been published. 14,15 Overall, 73.48% of the patients in the study showed stages 3 and 4 of triggering, which meant that the patients had irregular finger movement and sporadic finger locking but that these symptoms were actively correctable.…”
Section: Discussionmentioning
confidence: 95%
“…Similar results have already been published. 14,15 Overall, 73.48% of the patients in the study showed stages 3 and 4 of triggering, which meant that the patients had irregular finger movement and sporadic finger locking but that these symptoms were actively correctable.…”
Section: Discussionmentioning
confidence: 95%